A possible role of Werner helicase interacting protein 1 (WRNIP1) in the Fanconi anemia DNA repair pathway - Bulsiewicz, A (2016)
The Fanconi anemia (FA) pathway plays a crucial role in resolving DNA interstrand crosslinks (ICLs), which can form as a result of DNA damage by genotoxic agents (Lopez-Martinez et al., 2016). The exact mechanism of FA pathway action is unknown, although 21 proteins have been identified as its components, which, in turn, form at least three known groups, i.e. core, FANCD2/FANCI and downstream effector proteins (Mamrak et al., 2016; Ceccaldi et al., 2016). The FANCD2/FANCI complex is multi-phosphorylated and monoubiquitinated on both FANCD2 and FANCI after ICL-inducing damage. However, how FANCD2/FANCI complex is recruited to damaged chromatin remains elusive (Cohn and D’Andrea, 2008). This project investigates whether WRNIP1 can function as a protein operating in the Fanconi anemia pathway and examines its interaction with FANCD2 and FANCI. It was demonstrated here that WRNIP1 behaved similarly to the Fanconi anemia proteins because its depletion resulted in higher sensitivity of cells to the ICL-inducing agents, i.e. mitomycin C (MMC), TMP combined with UVA irradiation as well as cisplatin. Moreover, it was demonstrated that WRNIP1 partially rescued the sensitivity of WRNIP1-depleted cells after their complementation. It has been demonstrated that following treatment with genotoxic agents of cells and their subsequent fractionation, WRNIP1 did not show any significant increase in its nuclear fraction levels. Furthermore, WRNIP1-deficient cells treated with ICL-inducing agents and subsequently fractionated did not affect the ubiquitination patterns of FANCD2 nor did WRNIP1 depletion affect the formation of FANCD2 repair foci. These data might indicate that WRNIP1 was already present in the nucleus at the levels necessary to repair DNA. However, the lack of alteration in the FANCD2 ubiquitination and absence of effect of FANCD2 foci formation might suggest that WRNIP1 acted downstream of FANCD2 in the Fanconi anemia pathway or that there was no interaction between these two proteins. Therefore, this part of the project did not establish a functional link between FANCD2 and WRNIP1. It was demonstrated for the first time by in vitro binding analysis that WRNIP1 could bind to the two established components of the Fanconi anemia pathway, i.e. FANCD2 and FANCI. This result was corroborated by a subsequent study which revealed that FANCD2, FANCI and WRNIP1 could also form a complex together. It was shown that WRNIP1 bound to FANCD2 independently of FANCI. The in vitro binding analysis also attempted to map a WRNIP1’s domain which would be responsible for interaction with FANCD2. However, the three investigated WRNIP1 deletion mutants were shown to bind FANCD2. This outcome indicated the possibility that either WRNIP1 amino acid sequences located in between the three previously-generated regions were responsible for FANCD2-WRNIP1 interaction or, alternatively, WRNIP1 might bind to FANCD2 via two or more domains. It was also shown here that WRNIP1 was purified in two forms, one of which was demonstrated to be ubiquitinated. However, the type of ubiquitination has not been determined yet. It was demonstrated that deletion of WRNIP1's UBZ domain abrogates its ubiquitination but the consequences of this phenomenon must still be established.